Hyperintense cortical signal on magnetic resonance imaging reflects focal leukocortical encephalitis and seizure risk in progressive multifocal leukoencephalopathy. Issue 5 (28th April 2014) - Khoury, Michael N.; Alsop, David C.; Agnihotri, Shruti P.; Pfannl, Rolf; Wuthrich, Christian; Ho, Mai‐Lan; Hackney, David; Ngo, Long; Anderson, Matthew P.; Koralnik, Igor J.
<x xml:space="preserve">Abstract</x> Objective To determine the frequency of hyperintense cortical signal (HCS) on T1‐weighted precontrast magnetic resonance (MR) images in progressive multifocal leukoencephalopathy (PML) patients, its association with seizure risk and immune reconstitution inflammatory syndrome (IRIS), and its pathologic correlate. Methods We reviewed clinical data including seizure history, presence of IRIS, and MR imaging scans from PML patients evaluated at our institution between 2003 and 2012. Cases that were diagnosed either using cerebrospinal fluid JC virus (JCV) polymerase chain reaction, brain biopsy, or autopsy, and who had MR images available were included in the analysis (n = 49). We characterized pathologic findings in areas of the brain that displayed HCS in 2 patients and compared them with isointense cortex in the same individuals. Results Of 49 patients, 17 (34.7%) had seizures and 30 (61.2%) had HCS adjacent to subcortical PML lesions on MR images. Of the 17 PML patients with seizures, 15 (88.2%) had HCS compared with 15 of 32 (46.9%) patients without seizures (p = 0.006). HCS was associated with seizure development with a relative risk of 4.75 (95% confidence interval = 1.2–18.5, p = 0.006). Of the 20 patients with IRIS, 16 (80.0%) had HCS compared with 14 of 29 (49.3%) patients without IRIS (p = 0.04). On histological examination, HCS areas were associated with striking JCV‐associated demyelination of cortical and subcortical U fibers, significant macrophage infiltration, and a pronounced reactive gliosis in the deep cortical layers. Interpretation Seizures are a frequent complication in PML. HCS is associated with seizures and IRIS, and correlates histologically with JCV focal leukocortical encephalitis. Ann Neurol 2014;75:659–669